The Politics of Ear Mutilation: Cropping an Enslaved Person in the Gospel Passion Narratives - Soon, Isaac T. (Journal for the study of the New Testament, 2024)
This article challenges a slaveholder perspective of the treatment of the high priest’s enslaved agent in the canonical gospels. It seeks to demonstrate how ancient traditions and practices of ear cropping and facial mutilation, especially of enslaved folks, give insight into the significance of the enslaved agent’s treatment in the gospels. Far from being a mere plot device, the enslaved person who is maimed is a site of political knowledge that has simultaneous implications for our understanding of the enslaved agent themselves, the mutilating disciple, and Jesus. While the vast majority of interpreters of the passage view the maiming of Malchus’s ear as unimportant, a close analysis of contexts where ears are mutilated, maimed, and cropped provides a useful framework for rereading the episode in each of the gospels. After analyzing the contexts of ear cropping, from ancient Southwest Asia to second-century literature, I re-read each version of the episode from a narrative-critical point of view. In light of ancient accounts of cropping and mutilation, I find that the mutilating disciple’s behavior in the gospels was not heroic, that the enslaved person retains no agency, and that Jesus is complicit in the disciple’s actions against the high-priest’s agent.